INTRAOPERATIVE PHOTODYNAMIC THERAPY IN PATIENT WITH STAGE IIIC BREAST CANCER (8 YEARS WITHOUT RECURRENCE) - A. D. Kaprin; E. V. Rasskazova; E. V. Filonenko; E. K. Saribekyan; A. D. Zikiryakhodzhaev; V. I. Chissov (Biomedical Photonics, 2017)
The article presents  a clinical observation  of the patient  of 38 y.o. with cancer of the left breast stage IIIC урТ4bN3М0L1V1. On the 1st  step of the treatment the patient  had 2 courses of CAF neoadjuvant chemotherapy, on the 2nd  step – extended radical mastectomy on the left with intraoperative photodynamic therapy and closure of the defect with ТRАМ-flap, on the 3rd step – continuation of the chemotherapy (8 courses), on the 4th  step  – radiation  therapy  to the chest wall on the left and zones of regional lymph drainage, targeted therapy  with herceptin  a (1 year). Four years later a silicone implant was inserted  into the left breast. Corrective surgery (reduction  mammoplasty on the right side) was performed in april, 2017. Currently, the patient has remission of the disease of the left breast, the period of remission accounts for 8 years.